PEMANFAATAN LIMBAH AMPAS TAHU DESA NGASINAN ETAN, GEBANG, MASARAN, SRAGEN - Haryanto, Aris Tri; Dewi, Septiana Novita; Riyadi, Joko Sekti (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2020)
Ngasinan Etan Village is one of the villages located in Gebang Village. The livelihood as a small businessman from this village is very possible because of the very strategic location close to the Gebang traditional market and the traditional Pucuk padar. The increase in tofu production in Gebang village has positive and negative impacts, the positive impact is that it has increasingly increased the MSMEs of Gebang village and can improve the welfare of the community. The negative impact is the amount of tofu waste that is released, causing unpleasant odors. The main problem asked by these entrepreneurs is the accumulation of dense waste that often affects the environment which causes air pollution as it is delicious. With the consideration of the community specifically tofu entrepreneurs, and with the thought of solutions based on existing theories and research results, the first priority that needs to be done is to improve the management of solid waste management in tofu. Improvements to the tofu mill's solid waste management methods, by providing an understanding of how to manage tofu's basic waste into food products. Utilization of tofu waste can be done by drying and made with a variety of processed products that can be consumed by the community, for example, processed into tempe gembus, beef food, fish feed sources, nata de soya production, tofu waste as organic fertilizer, tofu waste, tofu waste to poultry feed and tofu pulp into processed crackers.Tofu, Gebang, Masaran, Sragen waste